2016
DOI: 10.1002/aelm.201600229
|View full text |Cite
|
Sign up to set email alerts
|

All‐Carbon Thin‐Film Transistors as a Step Towards Flexible and Transparent Electronics

Abstract: silicon wafer, TFTs can be fabricated on various types of rigid or flexible substrates. [1] TFTs fabricated on glass are primarily used for driving circuits in the liquid-crystal displays of televisions, computer monitors, and mobile phones, etc. Well-established TFT technologies based on amorphous silicon and polycrystalline silicon are well-suited for large-area, highresolution panels, e.g., six pieces of 65-and 75-inch TFT arrays can be fabricated on a 10.5th generation glass substrate. [2] However, TFTs ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 226 publications
(298 reference statements)
1
22
0
Order By: Relevance
“…Employing spin coated ZrO x film (500 °C) as the dielectric layer, Dodabalapur et al demonstrated complementary inverters ( Figure a) and high speed ring oscillators (Figure b) using inkjet printed SWCNTs (p‐type) and ZTO (n‐type) semiconductors . CNTs have been attracting great interest for TFT integration over past two decades due to their high mobility, chemical stability, excellent mechanical flexibility, and potential for various applications (e.g., ICs, displays, and sensors) . Figure c shows output and transfer curves for ZTO and SWCNT TFTs, exhibiting μ FE = 4.4 and 1.7 cm 2 V −1 s −1 in the saturation region, respectively.…”
Section: Recent Achievements Of Oxide High κ Dielectrics Using Solutimentioning
confidence: 99%
“…Employing spin coated ZrO x film (500 °C) as the dielectric layer, Dodabalapur et al demonstrated complementary inverters ( Figure a) and high speed ring oscillators (Figure b) using inkjet printed SWCNTs (p‐type) and ZTO (n‐type) semiconductors . CNTs have been attracting great interest for TFT integration over past two decades due to their high mobility, chemical stability, excellent mechanical flexibility, and potential for various applications (e.g., ICs, displays, and sensors) . Figure c shows output and transfer curves for ZTO and SWCNT TFTs, exhibiting μ FE = 4.4 and 1.7 cm 2 V −1 s −1 in the saturation region, respectively.…”
Section: Recent Achievements Of Oxide High κ Dielectrics Using Solutimentioning
confidence: 99%
“…In particular, the ability to realize flexible thin‐film transistors (TFTs), which are key driving/switching component of wearable electronics, offers much freedom on the target substrates. Therefore, a variety of functional materials focusing on semiconductors have been extensively explored for realizing competitive flexible TFTs, including traditional silicon, organics, oxides, carbon nanotubes (CNTs), and emerging 2D materials . Furthermore, because representative flexible or stretchable platforms, such as polymer‐based plastic and polydimethylsiloxane (PDMS) substrates, are difficult to utilize in traditional microfabrication, the development of alternative processes that can be employed for implementing low‐cost, large‐area, flexible, and biocompatible electronics is key to meet this demand.…”
Section: Introductionmentioning
confidence: 99%
“…This review highlights recent progress in inkjet‐printed TFTs to achieve improved electrical performance and their emerging electronics applications. Although several excellent reviews have already introduced printable organic, oxide, and 2D materials for large‐area TFT applications, for example, high‐speed printed circuits and transparent CNT‐based applications, the overarching aim of this review is to provide an overview of the recent efforts to realize high‐performance inkjet‐printed TFTs based on various channel materials and switching mechanisms as well as fundamental inkjet printing technology. The issues raised in the field of inkjet‐printed organic, metal‐oxide, low‐dimension thin‐film transistors in electronic and material perspectives would be systematically described, and then the currently promising strategies to address these issues will be introduced.…”
Section: Introductionmentioning
confidence: 99%
“…Transparent transistor arrays with sufficient mechanical flexibility have been spotlighted as key technologies for flexible opto- and nanoelectronic devices such as light-emitting diode, display, touch panel, and electronic skin . Use of transparent materials and dimensional reduction of nontransparent materials have been the main approaches in fabrication of transparent flexible transistors.…”
mentioning
confidence: 99%